Effect of hydroxypropyl methylcellulose-based coating on the formation of polar compounds in French fries - Yuan, Liyang; Tan, Chin Ping; Liu, Yuanfa; Xu, Yong Jiang (Elsevier, 2025)
Excessive oil uptake and formation of polar components during deep-frying pose potential risks to food quality and safety. Three hydroxypropyl methylcellulose (HPMC; E50, E1500, and E4000), with different degree of methyl and hydroxypropyl substitution, were coated on the surface of potato strips before deep-frying. The optimal coating concentrations were determined based on the oil absorption and water loss of fried products. Compared to uncoated samples, total polar compounds (TPC) in E50-, E1500-, and E4000-coated samples were reduced by 16.12 %, 12.08 %, and 22.02 %. Additionally, coatings with E50, E1500, and E4000 decreased the proportion of oxidized triglyceride monomer (ox-TGM) by 5.57 %, 2.70 %, and 8.71 %, and total epoxy triglycerides (ETGs) by 29.96 %, 15.51 %, and 33.43 %, respectively. No significant difference in texture and sensory attributes between coated and uncoated fries were observed. Furthermore, canonical correlation analysis uncovered significantly positive correlations between ETG level in fries and hydroxypropyl content in HPMC.